Sedimentation and contaminant criteria for watershed planning and management: completion report - Shen, Hsieh Wen, 1931-, author; Environmental Resources Center, Colorado State University, publisher (Colorado State University. Libraries, 1972)
When precipitation reaches its watershed, part of the water will infiltrate and percolate through the soil as ground water and a large portion of water will form surface runoff. This report is to describe a study on the effect of vegetation on the flow rates, sediment yield, and dispersion of contaminants (such as herbicides, pesticides, and radioisotopes) attached to particles during surface runoffs in watersheds. A model to estimate the resistance of flow due to various combinations of tall vegetation (such as trees) on the order of flow depths is given here. An empirical curve by regression to estimate the flow resistance with large rigid roughness (short vegetation such as grasses) in the order of normal boundary roughness is developed. The possibility of applying this curve to flexible roughness has also been explored. An analytical method to investigate the effect of vibrating flexible roughness elements in flow rate is also presented. The relative effect of various combinations of tall vegetation on the reduction of sediment yields based on the reduction of flow rates is studied. This should be rather useful in determining the relative effect on sediment yields by clear cutting and other selective cutting of forest lumber. The effect of rainfall on these sheet flows is investigated and a simplified method to estimate the rainfall effect on flow resistance is also developed. The dispersion of contaminated bed particles for different time and space can be found from graphical solutions as illustrated here. An empirical curve to estimate the sediment bed material load for various flow conditions is found.
CER71-72HWS48.
June, 1972.
The work upon which this report is based was supported in part by funds provided by the United States Department of the Interior, Office of Water Resources Research, as authorized by the Water Resources Research Act of 1964, and pursuant to grant agreement No. 14-01-0001-1435.
Circulating copy deaccessioned 2020.
Keywords: Watersheds -- Research; Watershed management; Runoff